(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
The present research works were conducted to find out the variation in morphological traits and their relationship in Brassica materials at C7 (Colchiploid) alloplasmic populations and F5 generations with respect to their parents. Among the 19 Brassica progeny lines representing the cross products (Brassica napojuncea) of C7 generation of Brassica napus and Brassica juncea (BINA sharisha 5 x Daulot: colchiploid-C7) and F5 generations with their parents, inter-species EG2 (Brassica napus x Brassica juncea) and EG1 (Brassica napus x Brassica juncea) showed better agronomic performance. Phenotypic characters of the genotypes were closely associated with each other for both normal correlation coefficients and Spearmans rank correlation coefficients. The total relative ranking ranged from 1 to 20 and the first rank was estimated for the genotype EG2 genotypes. The last rank was estimated for the genotype ED1 (Brassica napus x Brassica napus). Out of 55 associations, which found in the correlation study, 10 associations were found highly significant at the morphological level. Flower set per plant (self) showed highly significant positive association with total number of siliqua per plant (self) (r = 0.934**) but the significant negative association of the total number of siliqua per plant (self) with siliqua length was very strong (-0.489*). There was a genetic basis of association in most of the cases of pairs of relations. The Spearmans rank correlation test was studied to compare the morphological characterization for distinguishing genotypes. In this present study, this test presented 12 relationships that showed 10 positive significant and two negative significant correlations. In normal correlation coefficients 10 significant associations were found but 12 associations in Spearmans rank correlation. In these techniques, number of flower set per plant (self) had highly significant positive correlation with total number of siliqua per plant (rs = 0.817**). The days to 50 % flowering and number of seed per siliqua (self) had significant negative correlation with number of seed per siliqua (open) (rs = -0.546**) and number of flowers set per plant (open) (rs = -0.563*), respectively. Finally, the study suggested that some yield related traits such as flower set per plant, number of siliqua per plant, seed per siliqua and days to 50% flowering can be selected and used in breeding program for future increasing the grain yield of rapeseed.